Urban uses change an analytical study using geographic information systems/Kufa city as a model. Issue 1 (31st December 2022) - Hani Al-Tamimi, Ahmed; Alnasrawy, Arkan Ali Manji; Halais Al- Hatmi, Mehdi; AL-Ansari, Nadhir; Al-Mamoori, Sohaib Kareem; Jiddy, Zena Ayad Jabber
Abstract: Change is considered a prominent feature of urban areas because of the various services and functions in cities, with complex functional relations. The study aims to build an informational foundation for urban planners and designers on the effects resulting from the imbalance in the organization and proportions of urban land uses, which in turn affects the performance of its functions in the city and its changes, and thus the necessity of using modern technologies to identify and define urban problems in cities, especially those related to land uses. An analytical approach to the research was taken, adopting geographic information systems as a tool for research by studying the reality of the region and determining the changes occurring from the functional side for the periods of 2, 003, 200, 820, 132, 018. These periods witnessed substantial development and changes at the city and country levels. Through the results of the study, the changes were identified, remedies suggested, positive aspects were strengthened, and negative phenomena were reduced. The conclusions reached by the study indicate that planning for the use of the land is a very important practical aspect of achieving the needs of the population and limiting the noncultural aspects of expansion. Deliberate and planned change can generate positive results and vice versa.